New horizons in management of heart failure in older patients. (7th November 2019) - Stefil, Maria; Manzano, Luis; Montero-PéRez-Barquero, Manuel; Coats, Andrew J S; Flather, Marcus
Abstract: Heart failure has a high prevalence in older populations, is a common and growing cause for hospital admission and carries a high risk of morbidity and mortality. Important co-morbidities in older patients with heart failure include atrial fibrillation, renal impairment, hypertension and anaemia. Diagnosing and managing heart failure in older patients are complicated due to atypical presentations, co-morbidities and a relative lack of evidence for commonly used treatments in younger patients. The growing epidemic of heart failure is also under-recognised and resourced in most health systems. Despite potential differences, we recommend that the basic approach to manage heart failure patients with an ejection fraction (EF) of <40% should be the same in older and younger. These treatments need to be started at low doses and titrated slowly along with the management of co-morbidities. Older patients with EF 40–49% can be treated in a similar manner to those with <40%, while the treatment of those with EF ≥50% is pragmatic in nature based on symptom control and management of co-morbidities although the evidence base for these recommendations is lacking. Overall management must be holistic and continuous based on the patient's social circumstances and ongoing needs. Finally, there is an urgent need for more research, evidence and resources directed towards older populations with heart failure to improve their care and the quality of life.